Preparation method of Si-based MIS junction photocathode synergistically regulated by Ti-Ag and application of Si-based MIS junction photocathode synergistically regulated by Ti-Ag in carbon dioxide reduction
Patent Information
- Application Number
- CN202611348451.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-10-09
AI Technical Summary
[0009]然而,目前公开报道和现有专利中,针对Ti界面层调控的Si基MIS结光阴极及其在二氧化碳还原中的应用研究仍相对有限
(1)本发明采用带有表面氧化层的Si基底作为吸光材料,通过在绝缘层与金属层之间引入Ti界面层,构建了结构稳定、界面可调的Si基金属-绝缘体-半导体(MIS)结光阴极。所制备的光阴极具有较高的光电压、优异的界面电荷分离与传输能力以及良好的光电化学运行稳定性,能够实现光生载流子的高效收集与定向传输,从而有效提高二氧化碳还原反应的光电催化性能和太阳能到化学能的转化效率。
Smart Images

Figure CN122879736A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photoelectrocatalysis technology, specifically relating to a method for preparing a Ti-Ag synergistically regulated Si-based MIS junction photocathode and its application in carbon dioxide reduction. Background Technology
[0002] Photoelectrochemical (PEC) technology can directly convert solar energy into chemical energy and drive the reduction of carbon dioxide to produce high-value-added carbon-based fuels or chemicals such as carbon monoxide, formic acid, methanol, and methane. It combines the advantages of solar energy storage and CO2 resource utilization, thus attracting widespread attention in the fields of renewable energy conversion and carbon neutrality. Related research indicates that the key to PEC-CO2 reduction lies in the semiconductor's light absorption, the efficient separation and transport of photogenerated carriers, and the synergistic optimization of CO2 adsorption, activation, and surface catalytic reaction processes at the electrode / electrolyte interface.
[0003] Si, with its moderate bandgap, strong visible light absorption, abundant reserves, low cost, and mature semiconductor processing technology, is an important candidate material for constructing high-performance PEC photocathodes. In recent years, researchers have applied Si-based photocathodes to carbon dioxide reduction systems. For example, Li et al. reported a Si / TiO2 type photocathode with an osmium complex as the catalytic center, achieving highly selective CO2 to CH4 conversion, indicating that Si-based photocathodes have promising applications in solar-driven CO2 reduction.
[0004] Metal-insulator-semiconductor (MIS) structures have been used in high-efficiency silicon-based photoelectric conversion devices since the 1970s due to their ability to effectively control the bending of semiconductor surface bands, suppress interfacial recombination, and improve selective carrier transport. MA Green was one of the first to systematically propose and study MIS solar cell structures, pointing out that MIS structures can be used to improve the performance of silicon-based devices, and laying the theoretical foundation for the subsequent development of silicon-based MIS photoelectrodes.
[0005] In the study of non-uniform interfaces in MIS structures, Nakato et al. were among the first to discover that constructing discontinuous metal layers or ultrafine metal particle modification layers on semiconductor surfaces could yield photovoltages higher than those expected in traditional continuous metal / semiconductor Schottky junctions. Their subsequent research further demonstrated that the size, distribution, and spacing of the surface metal particles significantly affect the interfacial barrier and the separation and transport of photogenerated carriers. This type of research provides important evidence for improving the performance of Si-based photoelectrodes by constructing non-uniform interfaces.
[0006] In recent years, Kenney et al. further reported on electrodeposited non-uniform MIS junction photoanodes, demonstrating that the height of the spatially non-uniform barrier can significantly improve the device's photovoltage. Subsequently, Ji et al. further demonstrated through interface engineering that synergistic modulation of the metal-insulator interface and the insulation-semiconductor interface can simultaneously improve the photovoltage and stability of the MIS photoelectrode. These studies illustrate that the functional layers and their interface states in the MIS structure have a decisive influence on device performance.
[0007] For Si-based photocathodes, the MIS structure not only helps improve photovoltage but also enhances device stability and surface reaction kinetics through interface engineering. Esposito, Levin, Moffat, and A. Alec Talin et al. reported that employing a high-quality thermally oxidized SiO2 layer and a bilayer metal catalytic structure can significantly improve the charge collection and hydrogen evolution performance of Si-based MIS photocathodes, and pointed out that the interfacial inversion layer and surface charge transport behavior play a crucial role in device performance. This study further illustrates that a high-quality interfacial layer is of great significance for improving the carrier separation and transport capabilities of Si-based MIS photocathodes.
[0008] Furthermore, Ti-based interface layers or TiO2-related interface layers have shown significant application value in Si-based photoelectrode interface engineering due to their excellent chemical stability, interfacial adhesion, and bandgap modulation capabilities. Existing research has demonstrated that TiO2 protective / interface layers can improve Si surface stability and promote interfacial charge transport, thus attracting widespread attention in Si-based photocathodes and photoanodes.
[0009] However, research on Si-based MIS junction photocathodes with Ti interface layer modulation and their application in carbon dioxide reduction is still relatively limited in publicly reported and existing patents. Existing technologies typically suffer from complex fabrication processes, high equipment requirements, insufficient interface modulation precision, and difficulty in simultaneously achieving high photovoltage, high carbon dioxide reduction selectivity, and long-term operational stability. Therefore, it is still necessary to develop a novel Ti interface layer modulation structure for Si-based MIS junction photocathodes that is simple to fabricate, has strong interface controllability, low raw material costs, is suitable for large-scale fabrication, and can effectively improve the photovoltage, carrier separation efficiency, and operational stability of Si-based MIS junction photocathodes in PEC-CO2 reduction. These technological needs align with the current development direction of Si-based MIS interface engineering and non-uniform barrier modulation. Summary of the Invention
[0010] To address the problems existing in the prior art, this invention provides a method for preparing a Ti-Ag synergistically regulated Si-based MIS junction photocathode and its application in carbon dioxide reduction. The photocathode uses a silicon-based semiconductor substrate as the light-absorbing layer, and on its surface, a silicon oxide interface layer, a Ti metal interface layer, and an Ag catalytic layer are constructed to form a p-Si / SiO2 layer.x A Ti / Ag type MIS junction photocathode structure is presented. A silicon oxide interface layer is used to regulate the surface state of the silicon substrate and form an insulating interface. A Ti metal interface layer improves the interfacial contact quality and carrier separation and transport behavior of the MIS junction. An Ag catalytic layer promotes the carbon dioxide reduction reaction. By synergistically controlling the thickness windows of the Ti and Ag layers, the interfacial transport process of photogenerated carriers can be optimized, reducing interfacial charge recombination and transport impedance, thereby improving the photocathode's photoelectric response and product selectivity in the carbon dioxide reduction reaction. This photocathode has a simple fabrication process, obtained through steps such as cleaning, surface oxidation, metal layer deposition, and electrode encapsulation. It can achieve carbon dioxide reduction under illumination in a carbon dioxide-containing electrolyte, preferentially producing carbon monoxide as the product. It possesses controllable structure, simple preparation, and application value suitable for photoelectrocatalytic carbon dioxide conversion.
[0011] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of the present invention provides a Si-based MIS junction photocathode with Ti / Ag thickness synergistic control, comprising a silicon-based semiconductor substrate, a silicon-containing oxide interface layer disposed on the surface of the silicon-based semiconductor substrate, a Ti-containing metal interface layer disposed on the surface of the silicon-containing oxide interface layer, and an Ag-containing catalytic layer disposed on the surface of the Ti-containing metal interface layer; wherein the silicon-based semiconductor substrate, the silicon-containing oxide interface layer, and the Ti-containing metal interface layer together constitute a MIS junction structure, and the Ag-containing catalytic layer is used to promote the carbon dioxide reduction reaction.
[0012] Further, the silicon-based semiconductor substrate is a p-type silicon-based substrate, which is any one of p-type single-crystal silicon wafers, p-type polycrystalline silicon wafers, p-type silicon thin-film substrates, p-type silicon micro / nanostructure substrates, and p-type doped silicon-based substrates; the crystal orientation of the silicon-based semiconductor substrate is... <100> , <110> or <111> .
[0013] Furthermore, the silicon-containing oxide interface layer is SiO2. x Where 0 < x ≤ 2; the SiO x It is at least one of non-stoichiometric silicon oxide, oxygen-deficient silicon oxide, and hydroxyl-containing silicon oxide; the silicon oxide interface layer is at least one of native oxide layer, chemical oxide layer, thermal oxide layer, ozone oxide layer, plasma oxide layer, electrochemical oxide layer, atomic layer deposition oxide layer, and chemical vapor deposition oxide layer; the thickness of the silicon oxide interface layer is 0.3-20 nm, preferably 2-5 nm.
[0014] Furthermore, the Ti-containing metal interface layer is a Ti elemental layer, a Ti alloy layer, a partially oxidized Ti layer, or a TiO2 layer. x Layer, Ti / TiO xAt least one of the composite layers; the thickness of the Ti-containing metal interface layer is 0.1-50 nm, preferably 1-20 nm, and more preferably 2-10 nm.
[0015] Further, the Ag-containing catalyst layer is at least one of dense Ag elemental layer, Ag alloy layer, Ag nanoparticle layer, Ag island layer, Ag semi-continuous thin film layer, porous Ag layer, and Ag-containing composite catalyst layer; the thickness of the Ag-containing catalyst layer is 0.1-100 nm, preferably 1-50 nm, and more preferably 2-20 nm.
[0016] A second aspect of this invention provides a method for fabricating a Si-based MIS junction photocathode with synergistically regulated Ti / Ag thickness, comprising the following steps: Step S1: Clean the silicon-based semiconductor substrate with the natural oxide layer; Step S2: Oxidize the cleaned silicon-based semiconductor substrate; Step S3: A Ti-containing metal interface layer and an Ag-containing catalyst layer are sequentially deposited on the surface of the oxidized silicon-based semiconductor substrate to obtain p-Si / SiO. x / Ti / Ag sample; Step S4: An ohmic contact is formed on the side of the silicon-based semiconductor substrate where no functional layer is deposited. The silicon-based semiconductor substrate is connected to an external circuit through a conductive connection material. An insulating encapsulation material is used to encapsulate the back and edge of the electrode, so that the back and edge of the electrode are insulated from the electrolyte. Only the working area on the side containing the Ag catalyst layer is kept in contact with the electrolyte to form a photocathode.
[0017] Further, in step S1, the cleaning treatment is at least one of organic solvent cleaning, deionized water cleaning, acid washing, alkaline washing, ultrasonic cleaning, ultraviolet ozone cleaning, plasma cleaning, and hydrofluoric acid treatment; in step S2, the oxidation treatment is at least one of natural oxidation, chemical oxidation, thermal oxidation, wet oxidation, ozone oxidation, ultraviolet ozone oxidation, oxygen plasma oxidation, electrochemical oxidation, atomic layer deposition, and chemical vapor deposition; in step S3, the deposition method of the Ti-containing metal interface layer and the Ag-containing catalyst layer is any one of thermal evaporation, electron beam evaporation, magnetron sputtering, atomic layer deposition, chemical vapor deposition, pulsed laser deposition, electrochemical deposition, solution deposition, and chemical reduction deposition; the deposition rates of the Ti-containing metal interface layer and the Ag-containing catalyst layer are 0.001-1. nm / s; In step S4, the ohmic contact material is at least one of indium gallium alloy, indium, gallium, aluminum, silver, and gold, preferably indium gallium alloy. The indium gallium alloy is coated on the area on the back of the silicon wafer where no functional layer is deposited to reduce the back contact resistance and improve the electrode conductivity. The conductive connection material is at least one of conductive silver paste, conductive carbon paste, metal wire, metal foil, and conductive adhesive, preferably conductive silver paste. The insulating encapsulation material is at least one of epoxy resin, silicone rubber, polyimide, and polytetrafluoroethylene, preferably epoxy resin.
[0018] Further, step S1 specifically involves cleaning and drying the silicon wafer with the natural oxide layer, immersing it in a 2 wt.% HF aqueous solution for 1-10 min, and then rinsing and drying it with ultrapure water.
[0019] Furthermore, the thickness of the natural oxide layer SiO2 is 0.5-3 nm, and the SiO2 after being treated with piranha solution... x The thickness is 0.1 nm-3 nm.
[0020] Further, step S2 specifically involves immersing the silicon wafer processed in step S1 in a piranha solution, then rinsing it with ultrapure water and drying it.
[0021] Furthermore, the piranha solution is a mixed solution with a volume ratio of H2SO4:H2O2 = 3:1, and the soaking time is 1 min to 24 h, preferably 12 h.
[0022] Furthermore, the deposition method for the Ti-containing metal interface layer and the Ag-containing catalyst layer is a thermal evaporation method, specifically, the thermal evaporation method involves: depositing p-Si / SiO... x After the sample is transferred to the vacuum deposition chamber, the vacuum deposition chamber is evacuated to 1×10⁻⁶. -3 Pa is below 5×10 Pa, and is further optimized to 5×10 Pa. -5Below Pa; the deposition rates of the Ti layer and the Ag layer are 0.001-1 nm / s, more preferably 0.01-0.2 nm / s, and even more preferably 0.02-0.1 nm / s, respectively.
[0023] Furthermore, in step S4, the effective working area of the photocathode is 0.1-2 cm². 2 The preferred size is 0.25-1cm. 2 .
[0024] The third aspect of the present invention provides an application of the above-mentioned Si-based MIS junction photocathode with Ti / Ag thickness synergistic control in the carbon dioxide reduction reaction. The Si-based MIS junction photocathode is used as the working electrode, and a constant potential or linear voltammetric scan is applied under illumination in an electrolyte containing carbon dioxide to induce a carbon dioxide reduction reaction.
[0025] Furthermore, the carbon dioxide reduction reaction system is a three-electrode system, wherein the counter electrode in the three-electrode system is any one of a Pt sheet electrode, a Pt wire electrode, or a graphite rod electrode, and the reference electrode is any one of an Ag / AgCl electrode, a saturated calomel electrode, or a Hg / HgO electrode.
[0026] Furthermore, the electrolyte containing carbon dioxide is a CO2-saturated KCl solution, and the concentration of the KCl solution is 0.1-1.0 mol / L, preferably 0.5 mol / L.
[0027] Furthermore, the electrolyte is saturated with carbon dioxide gas before use for 10-60 min, preferably 20-30 min; during the reaction process, carbon dioxide is continuously introduced, intermittently introduced, or a carbon dioxide atmosphere is maintained.
[0028] Further, the electrolyte comprises at least one selected from KCl, NaCl, LiCl, CsCl, NH4Cl, KHCO3, NaHCO3, K2CO3, Na2CO3, K2SO4, Na2SO4, phosphate buffer solution, and borate buffer solution, and the concentration of the electrolyte is 0.001-5.0 mol / L, preferably 0.05-1.0 mol / L; the illumination conditions are any one of simulated sunlight, visible light, near-infrared light, and monochromatic light irradiation, preferably AM 1.5G standard simulated sunlight irradiation, with an irradiance of 1-500 mW / cm². 2 Preferably 50-150 mW / cm 2 Further preferred is 100 mW / cm 2 The product of the reduction reaction is at least one of carbon monoxide, formate, methane, methanol, ethylene, and ethanol.
[0029] Furthermore, the constant potential is selected within the potential range of -1.2 to 0.2 V vs. RHE for electrolysis, and the electrolysis time is 30-60 min; preferably, a constant potential is selected within the potential range of -0.65 to -1.05 V vs. RHE for the carbon dioxide reduction reaction.
[0030] Furthermore, the linear voltammetric scan has a scanning range of -1.2 to 0.2 V vs. RHE and a scanning rate of 1-100 mV / s, preferably 20 mV / s.
[0031] Furthermore, the product of the carbon dioxide reduction reaction is carbon monoxide, while hydrogen is a competing product of the hydrogen evolution reaction.
[0032] In application, p-Si / SiO x SiO in / Ti / Ag photocathode x The interface layer is used to regulate the surface state of the silicon substrate and form an insulating interface. The Ti interface layer is used to regulate the interfacial contact state and carrier transport behavior between the metal layer, the insulating layer and the semiconductor. The Ag catalytic layer is used to provide active sites for the carbon dioxide reduction reaction. Through the synergistic regulation of the Ti interface layer and the Ag catalytic layer, the separation and transport efficiency of photogenerated carriers is improved and the interfacial charge transfer impedance is reduced, thereby improving the photoelectric response, operational stability and carbon monoxide selectivity of the Si-based MIS junction photocathode in the carbon dioxide reduction reaction.
[0033] Taking the photoelectrocatalytic carbon dioxide reduction process as an example, the inventors discovered that by sequentially constructing a silicon oxide interface layer, a Ti metal interface layer, and an Ag catalytic layer on the surface of a Si-based semiconductor substrate, a Si-based MIS junction photocathode with interface charge regulation function can be formed. Experimental results show that the introduction of the Ti interface layer can improve the photogenerated potential response of the photocathode, increasing it from approximately 217 mV to approximately 450 mV, and shortening the carrier decay time in transient absorption tests, indicating that it is beneficial for promoting the separation, extraction, and interface transport of photogenerated carriers. Furthermore, when the Ti layer thickness is approximately 6 nm, the photocathode exhibits a smaller interface charge transfer impedance in the impedance spectrum, while the reflectance spectrum shows that it has a more favorable light-harvesting ability. This indicates that a moderate Ti layer thickness can form a more effective MIS junction, promote the separation and interface transport of photogenerated carriers, and avoid the light shielding and additional transport losses caused by an excessively thick Ti layer, thus achieving a better balance between light absorption and electron transport. At the same time, the Ag catalytic layer, as the main active layer for the CO2 reduction reaction, can provide reaction sites for CO2 activation and CO generation. By synergistically regulating the Ti and Ag layers and using CO2-saturated KCl electrolyte as the reaction system, the p-Si / SiO2...x The / Ti / Ag photocathode can achieve selective conversion of CO2 to CO under illumination. The above results demonstrate that the present invention can achieve selective conversion of CO2 to CO using SiO2. x The / Ti / Ag multilayer interface design improves the interfacial charge transport process and reaction microenvironment of the Si-based photocathode, thereby enhancing its photoelectric response, stability, and product selectivity in the photoelectrocatalytic carbon dioxide reduction reaction.
[0034] Compared with the prior art, the beneficial effects of the present invention are: (1) This invention uses a Si substrate with a surface oxide layer as the light-absorbing material. By introducing a Ti interface layer between the insulating layer and the metal layer, a Si-based metal-insulator-semiconductor (MIS) junction photocathode with stable structure and tunable interface is constructed. The prepared photocathode has high photovoltage, excellent interfacial charge separation and transport capabilities, and good photoelectrochemical stability. It can achieve efficient collection and directional transport of photogenerated carriers, thereby effectively improving the photoelectrocatalytic performance of carbon dioxide reduction reaction and the conversion efficiency of solar energy to chemical energy.
[0035] (2) The present invention utilizes a Ti interface layer to enhance the Si / SiO2 interface. x By modulating the contact state, band structure, and carrier transport paths at the metal interface, the interface defect density and carrier recombination probability are reduced, enhancing the separation efficiency of photogenerated electrons and the interface transport capability. Simultaneously, this strategy helps improve the bonding stability between the metal functional layer and the substrate. This interface modulation strategy provides a new technical approach for designing efficient, stable, and low-cost Si-based MIS junction photocathodes, and is of great significance for improving the reactivity, product selectivity, and long-term stable operation of photoelectrodes in carbon dioxide reduction systems.
[0036] (3) The preparation method of the present invention is simple and easy to implement, with low requirements for equipment conditions and processes. It does not require complex and precise micro-nano processing. The raw materials are widely available and inexpensive, resulting in low preparation costs. It is easy to achieve precise control and repeated preparation, making it suitable for industrial and large-scale production. By adjusting the thickness of the Ti interface layer, the metal layer deposition conditions, and the interface structure parameters, the photoelectric performance and electrocatalytic performance of the Si-based MIS junction photocathode can be further optimized, thereby meeting the application requirements of different carbon dioxide reduction reaction systems.
[0037] (4) The Ti interface layer controlled Si-based MIS junction photocathode constructed in this invention not only has high photovoltage and excellent operational stability, but also exhibits good photoresponse characteristics and efficient electron utilization in the photoelectric reduction of carbon dioxide. It can be used for the conversion and preparation of carbon-based products such as carbon monoxide, formic acid, methanol, and methane. It has broad application prospects in the fields of solar energy conversion, carbon dioxide resource utilization, photoelectrocatalysis and clean energy. Attached Figure Description
[0038] Figure 1 p-Si / SiO prepared in this invention x Morphology, crystal structure and surface chemical state characterization of the / Ti / Ag photocathode; where (a) is an atomic force microscope image, (b) is an X-ray diffraction pattern, (c) is a high-resolution X-ray photoelectron spectrum of Ag 3d, and (d) is a high-resolution X-ray photoelectron spectrum of Ti 2p.
[0039] Figure 2 A comparison of photogenerated carrier separation and transport characteristics of Si-based photocathodes before and after introducing a Ti layer; where (a) and (d) are p-Si / SiO2, respectively. x / Ti / Ag photocathode and p-Si / SiO x The intermittent illumination potential response diagram of the / Ag photocathode, (b) and (e) are the transient absorption spectra of the corresponding photocathode, and (c) and (f) are the transient absorption kinetic fitting curves of the corresponding photocathode at 750 nm.
[0040] Figure 3 p-Si / SiO with different Ti layer thicknesses x Electrochemical impedance spectroscopy of the / Ti / Ag photocathode.
[0041] Figure 4 p-Si / SiO with different Ti layer thicknesses x Reflectance spectrum of / Ti / Ag photocathode.
[0042] Figure 5 p-Si / SiO with different Ti layer thicknesses x The Faraday efficiency of the / Ti / Ag photocathode for photocatalytic carbon dioxide reduction products under different applied potentials; where (a), (b) and (c) correspond to photocathodes with Ti layer thicknesses of 2 nm, 6 nm and 10 nm, respectively. Detailed Implementation
[0043] The specific embodiments of the present invention will be further described below. It should be noted that these descriptions are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0044] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the experimental materials used in the following embodiments are all available through conventional commercial channels.
[0045] The silicon wafer is boron-doped p-type single crystal Si(100); the Ti and Ag metal sources are high-purity metal evaporation sources; the hydrofluoric acid, sulfuric acid, hydrogen peroxide, potassium chloride and other reagents are all conventional analytical grade or electronic grade reagents; the resistivity of the ultrapure water is 18.2 MΩ·cm.
[0046] Example 1: Fabrication and application of a Si-based MIS junction photocathode with a Ti layer thickness of 6 nm. This embodiment provides a p-Si / SiO x The Ti / Ag photocathode has a Ti layer thickness of 6 nm and an Ag layer thickness of 10 nm. The specific steps are as follows: (1) p-Si / SiO x Substrate preparation Boron-doped p-type single-crystal Si(100) was used as the substrate. The silicon wafer was ultrasonically cleaned sequentially in ultrapure water, ethanol, acetone, and ultrapure water for 20 minutes in each step to remove particulate and organic contaminants from the silicon wafer surface. After cleaning, the silicon wafer was removed and dried with nitrogen gas.
[0047] Subsequently, the cleaned silicon wafers were immersed in a 2 wt.% HF aqueous solution for 5 min to remove the original natural oxide layer on the surface. After removal, they were rinsed with copious amounts of ultrapure water and dried with nitrogen. Then, the silicon wafers were immediately transferred to a piranha solution (a mixture of H₂SO₄ and H₂O₂ at a volume ratio of 3:1) for oxidation treatment for 1 h. After the oxidation treatment, the silicon wafer surface was thoroughly rinsed with copious amounts of ultrapure water and dried with nitrogen, resulting in a surface with SiO₂. x p-Si / SiO interface layer x Substrate.
[0048] (2) p-Si / SiO x Preparation of / Ti / Ag samples The p-Si / SiO obtained in step (1) x The substrate is placed in a vacuum thermal evaporation chamber with the polished surface of the silicon wafer facing the evaporation source. The vacuum chamber is evacuated to approximately 5 × 10⁻⁶ ppm before deposition. -5 Pa. Subsequently in p-Si / SiO x Ti and Ag layers were sequentially deposited on the substrate surface, with the Ti layer having a thickness of 6 nm and the Ag layer having a thickness of 10 nm. The deposition rate was controlled at 0.02–0.1 nm / s, and the film thickness was monitored using a quartz crystal microbalance. After deposition, p-Si / SiO2 was obtained. x / Ti(6 nm) / Ag(10 nm) sample. Its morphology, crystal structure and surface chemical state characterization diagrams are shown below. Figure 1 As shown, by Figure 1It can be seen that the p-Si / SiO prepared by this invention x A uniform and dense nanoparticle-like thin film structure was formed on the surface of the / Ti / Ag photocathode, without obvious large-scale cracks or severe agglomeration. XRD results showed that the film deposition did not damage the crystal structure of the Si substrate. XPS tests detected obvious Ag3d and Ti2p characteristic peaks, with Ag mainly exhibiting the characteristic of Ag2. 0 The characteristic binding energy of Ti was observed, and Ti exhibited the characteristic binding energy of the oxidized Ti species. These results indicate that Ti and Ag components have been successfully introduced into the Si-based photocathode, forming a structurally complete Ti / Ag composite interface, providing a foundation for constructing a Si-based MIS photocathode and realizing subsequent photoelectrocatalytic CO2 reduction.
[0049] (3) Packaging of photocathode The p-Si / SiO obtained in step (2) x A Ti(6 nm) / Ag(10 nm) sample was fabricated as a photocathode. Specifically, an indium gallium alloy was coated on the side of the silicon wafer without a functional layer to form a back ohmic contact; conductive silver paste was used to fix the silicon wafer to copper wires; then, epoxy resin was used to encapsulate the back and edges of the electrode to insulate the non-working area from the electrolyte, retaining only p-Si / SiO2. x The front area of the / Ti / Ag functional layer is in contact with the electrolyte. The effective working area of the photocathode is controlled to be 0.25-1 cm².
[0050] (4) Photoelectrocatalytic carbon dioxide reduction test.
[0051] The p-Si / SiO prepared in step (3) x A three-electrode photoelectrochemical reaction system was assembled, using a Ti (6 nm) / Ag (10 nm) photocathode as the working electrode, a Pt sheet electrode as the counter electrode, and an Ag / AgCl electrode as the reference electrode. A 0.5 MKCl aqueous solution was used as the electrolyte. Before the test, CO2 gas was continuously introduced into the electrolyte for 30 min to saturate it with CO2, and the CO2 atmosphere was maintained throughout the reaction.
[0052] During the test, AM 1.5G standard simulated sunlight was used as the light source, with an illuminance of 100 mW / cm². 2Under illumination, the photocathode was subjected to linear scan voltammetry and potentiostatic electrolysis. The linear scan voltammetry test covered a range of -1.2 to 0.2 V vs. RHE at a scan rate of 10 mV / s. The potentiostatic electrolysis test was performed at a constant potential within the range of -0.65 to -1.05 V vs. RHE for 30-60 min. Gas-phase products generated during electrolysis were detected using gas chromatography, while liquid-phase products were detected using nuclear magnetic resonance or ion chromatography.
[0053] Experimental results show that p-Si / SiO x The / Ti(6 nm) / Ag(10 nm) photocathode exhibits good photogenerated potential response, low interfacial charge transfer impedance, and relatively stable constant potential electrolysis response, enabling selective conversion of carbon dioxide to carbon monoxide in CO2-saturated KCl electrolyte.
[0054] Example 2: Fabrication and application of a Si-based MIS junction photocathode with a Ti layer thickness of 2 nm. The method in this embodiment is the same as in Embodiment 1, except that the thickness of the Ti layer deposited in step (2) is 2 nm and the thickness of the Ag layer is 5 nm, resulting in p-Si / SiO. x / Ti(2 nm) / Ag(5 nm) sample.
[0055] The sample was subjected to electrode encapsulation and photoelectrocatalytic carbon dioxide reduction tests according to steps (3) and (4) in Example 1. The experimental results show that when the Ti layer thickness is small, the photocathode can form a MIS junction structure and realize the carbon dioxide reduction reaction, but its interface charge regulation effect and reaction stability are different from those of the sample with a Ti layer thickness of 6 nm.
[0056] Example 3: Fabrication and application of a Si-based MIS junction photocathode with a Ti layer thickness of 10 nm. The method in this embodiment is the same as in Embodiment 1, except that the thickness of the Ti layer deposited in step (2) is 10 nm and the thickness of the Ag layer is 5 nm, resulting in p-Si / SiO. x / Ti(10 nm) / Ag(5 nm) sample.
[0057] The sample was subjected to electrode encapsulation and photoelectrocatalytic carbon dioxide reduction tests according to steps (3) and (4) in Example 1. Experimental results show that when the Ti layer thickness is further increased, the photocathode can still be used for photoelectrocatalytic carbon dioxide reduction reaction, but an excessively thick Ti layer may increase electron transport resistance, thereby affecting the interfacial reaction kinetics and electrode operating stability.
[0058] Example 4: Fabrication and application of a Si-based MIS junction photocathode with an Ag layer thickness of 5 nm. The method in this embodiment is the same as in Embodiment 1, except that the thickness of the deposited Ti layer in step (2) is maintained at 6 nm and the thickness of the Ag layer is 5 nm, resulting in p-Si / SiO. x / Ti(6 nm) / Ag(5 nm) sample.
[0059] The sample was subjected to electrode encapsulation and photoelectrocatalytic carbon dioxide reduction tests according to steps (3) and (4) in Example 1. p-Si / SiO₂ samples with different Ti layer thicknesses were obtained. x The electrochemical impedance spectroscopy, reflectance spectroscopy, and Faradaic efficiency diagrams of the photocatalytic carbon dioxide reduction products at different applied potentials for the / Ti / Ag photocathode are shown below. Figure 3 , Figure 4 , Figure 5 As shown, the experimental results indicate that when the Ag layer thickness is small, the surface coverage state and the number of catalytic active sites of the Ag catalyst layer change, thereby affecting the current response and product selectivity of the carbon dioxide reduction reaction.
[0060] Example 5: Fabrication and application of a Si-based MIS junction photocathode with an Ag layer thickness of 15 nm. The method in this embodiment is the same as in Embodiment 1, except that the thickness of the deposited Ti layer in step (2) is maintained at 6 nm and the thickness of the Ag layer is 15 nm, resulting in p-Si / SiO. x / Ti(6 nm) / Ag(15 nm) sample.
[0061] The sample was subjected to electrode encapsulation and photoelectrocatalytic carbon dioxide reduction tests according to steps (3) and (4) in Example 1. The experimental results show that as the Ag layer thickness increases, the continuity of the Ag catalyst layer and the distribution of reaction sites change, thereby further affecting the carbon dioxide reduction selectivity and constant potential operation stability of the photocathode.
[0062] Comparative Example 1: Fabrication and Application of a Si-based Photocathode Without an Introduced Ti Interface Layer The method of this comparative example is the same as that of Example 1, except that: in step (2), a Ti layer is not deposited, but rather on p-Si / SiO. x An Ag layer with a thickness of 10 nm was directly deposited on the substrate surface to obtain p-Si / SiO. x / Ag(10 nm) sample.
[0063] The sample was subjected to electrode encapsulation and photoelectrocatalytic carbon dioxide reduction testing according to steps (3) and (4) in Example 1. A comparison of the photogenerated carrier separation and transport characteristics of the Si-based photocathode before and after the introduction of the Ti layer is shown in the figure below. Figure 2 As shown, the test results indicate that, compared with p-Si / SiO2 with the introduction of a Ti interface layer, x Compared to the / Ti / Ag photocathode, the p-Si / SiO2 without the introduction of a Ti interface layer x The differences in photogenerated potential response, interfacial charge transport, and electrode operational stability between Ag photocathodes indicate that the Ti interfacial layer plays a crucial role in regulating SiO₂. x The metal catalyst layer plays an important role in the interface contact state and improving carrier separation and transport behavior.
[0064] In summary, the thickness of the Ti layer can be adjusted within the range of 0.1-50 nm, preferably 1-20 nm, and more preferably 2-10 nm; the thickness of the Ag layer can be adjusted within the range of 0.1-100 nm, preferably 1-50 nm, and more preferably 2-20 nm. Silicon-based semiconductor substrate, SiO2 x The interface layer formation method, metal layer deposition method, electrode encapsulation method, and electrolyte system can all be adjusted according to actual needs.
[0065] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.
Claims
1. A Si-based MIS junction photocathode with Ti / Ag thickness synergistic control, characterized in that, The method includes a silicon-based semiconductor substrate, a silicon-containing oxide interface layer disposed on the surface of the silicon-based semiconductor substrate, a Ti-containing metal interface layer disposed on the surface of the silicon-containing oxide interface layer, and an Ag-containing catalytic layer disposed on the surface of the Ti-containing metal interface layer; wherein the silicon-based semiconductor substrate, the silicon-containing oxide interface layer, and the Ti-containing metal interface layer together constitute a MIS junction structure, and the Ag-containing catalytic layer is used to promote the carbon dioxide reduction reaction.
2. The Si-based MIS junction photocathode with Ti / Ag thickness synergistic control according to claim 1, characterized in that, The silicon-based semiconductor substrate is a p-type silicon-based substrate, which can be any one of a p-type single-crystal silicon wafer, a p-type polycrystalline silicon wafer, a p-type silicon thin-film substrate, a p-type silicon micro / nanostructure substrate, or a silicon-based substrate treated with p-type doping; the crystal orientation of the silicon-based semiconductor substrate is... <100> , <110> or <111> .
3. The Si-based MIS junction photocathode with Ti / Ag thickness synergistic control according to claim 1, characterized in that, The silicon oxide interface layer is SiO x Where 0 < x ≤ 2; the SiO x It is at least one of non-stoichiometric silicon oxide, oxygen-deficient silicon oxide, and hydroxyl-containing silicon oxide; the silicon oxide interface layer is at least one of native oxide layer, chemical oxide layer, thermal oxide layer, ozone oxide layer, plasma oxide layer, electrochemical oxide layer, atomic layer deposition oxide layer, and chemical vapor deposition oxide layer; the thickness of the silicon oxide interface layer is 0.3-20 nm.
4. The Si-based MIS junction photocathode with Ti / Ag thickness synergistic control according to claim 1, characterized in that, The Ti-containing metal interface layer is a Ti elemental layer, a Ti alloy layer, a partially oxidized Ti layer, or a TiO2 layer. x Layer, Ti / TiO x At least one of the composite layers; the thickness of the Ti-containing metal interface layer is 0.1-50 nm.
5. The Si-based MIS junction photocathode with Ti / Ag thickness synergistic control according to claim 1, characterized in that, The Ag-containing catalyst layer is at least one of the following: dense Ag single layer, Ag alloy layer, Ag nanoparticle layer, Ag island layer, Ag semi-continuous thin film layer, porous Ag layer, and Ag-containing composite catalyst layer; the thickness of the Ag-containing catalyst layer is 0.1-100 nm.
6. A method for fabricating a Si-based MIS junction photocathode with Ti / Ag thickness synergistic control as described in any one of claims 1-5, characterized in that, Includes the following steps: Step S1: Clean the silicon-based semiconductor substrate with the natural oxide layer; Step S2: Oxidize the cleaned silicon-based semiconductor substrate; Step S3: A Ti-containing metal interface layer and an Ag-containing catalyst layer are sequentially deposited on the surface of the oxidized silicon-based semiconductor substrate to obtain p-Si / SiO. x / Ti / Ag sample; Step S4: An ohmic contact is formed on the side of the silicon-based semiconductor substrate where no functional layer is deposited. The silicon-based semiconductor substrate is connected to an external circuit through a conductive connection material. An insulating encapsulation material is used to encapsulate the back and edge of the electrode, so that the back and edge of the electrode are insulated from the electrolyte. Only the working area on the side containing the Ag catalyst layer is kept in contact with the electrolyte to form a photocathode.
7. The preparation method according to claim 6, characterized in that, In step S1, the cleaning treatment is at least one of organic solvent cleaning, deionized water cleaning, acid washing, alkaline washing, ultrasonic cleaning, ultraviolet ozone cleaning, plasma cleaning, and hydrofluoric acid treatment; in step S2, the oxidation treatment is at least one of natural oxidation, chemical oxidation, thermal oxidation, wet oxidation, ozone oxidation, ultraviolet ozone oxidation, oxygen plasma oxidation, electrochemical oxidation, atomic layer deposition, and chemical vapor deposition; in step S3, the deposition method of the Ti-containing metal interface layer and the Ag-containing catalyst layer is any one of thermal evaporation, electron beam evaporation, magnetron sputtering, atomic layer deposition, chemical vapor deposition, pulsed laser deposition, electrochemical deposition, solution deposition, and chemical reduction deposition; the deposition rates of the Ti-containing metal interface layer and the Ag-containing catalyst layer are 0.001-1. nm / s; In step S4, the ohmic contact material is at least one of indium gallium alloy, indium, gallium, aluminum, silver, and gold; the conductive connection material is at least one of conductive silver paste, conductive carbon paste, metal wire, metal foil, and conductive adhesive; the insulating encapsulation material is at least one of epoxy resin, silicone rubber, polyimide, and polytetrafluoroethylene.
8. The application of a Si-based MIS junction photocathode with Ti / Ag thickness synergistic control as described in any one of claims 1-5 in the carbon dioxide reduction reaction, characterized in that, Using the Si-based MIS junction photocathode as the working electrode, a constant potential or linear voltammetric scan is applied under illumination in a carbon dioxide-containing electrolyte to induce a reduction reaction of carbon dioxide.
9. The application according to claim 8, characterized in that, The electrolyte contains at least one of KCl, NaCl, LiCl, CsCl, NH4Cl, KHCO3, NaHCO3, K2CO3, Na2CO3, K2SO4, Na2SO4, phosphate buffer solution, and borate buffer solution, and the concentration of the electrolyte is 0.001-5.0 mol / L; the illumination conditions are any one of simulated sunlight, visible light, near-infrared light, and monochromatic light, and the light intensity is 1-500 mW / cm². 2 The product of the reduction reaction is at least one of carbon monoxide, formate, methane, methanol, ethylene, and ethanol.
10. The application according to claim 9, characterized in that, The product of the carbon dioxide reduction reaction is carbon monoxide.